Conceptualizing and exploring mathematics future teachers' learning of didactic notions (2009)
Exploring how future teachers learn in a training program requires taking into account what they are expected to learn and what kind of learning opportunities they are exposed to in their learning. In this paper we focus our attention on training programs that expect future teachers to develop their competencies in using certain didactic notions for analyzing a mathematical topic. We propose three ideas -meaning, technical use and practical use- for exploring future teachers' learning.